Future Directions for American Labor and Human Resources Policy - Kochan, Thomas; McKersie, Robert (Relations industrielles / Industrial Relations, 1989)
This paper discusses four commonly debated approaches toAmerican labor and human resource policy and argues for themost ambitious of these.